Reformasi Birokrasi Pemerintah Kota Semarang - Winasishadi, Ahmad Nuril; Taufiq, Ahmad (Journal of Politic and Government Studies, 2018)
This research is a policy studies that discuss about how Semarang City Government effort to implement the bureautratic reform as one of the realization of Presidential Instruction Number 1 Year 1995 with reference to The Restoration Improving the Quality of Government Agency Services to the People. The research uses descriptive qualitative research methods with data collection techniques through in-depth interviews dan documents. The main focus of this research is the extent of the bureauctratic reforms is running at Governmental Licensing Agency (GLA) of Semarang City, and what is the reform strategy that used in realizing the reform itself. Based on this research, the result that obtained is shows that bureaucratic reform effort which running at Governmental licensing agency is still facing some obstacles. Besides, the strategy that used is incremental strategy, that is strategy which held gradually. In implementation, The government is still found some obstacles, which is the technical team Semarang City GLA is still not exist at the bureau itself, but in other governmental bureau. The bureaucratic reform process is still remote from what to expect by the people, Semarang City GLA expected to solved the problems that caused the effectiveness and eficiencyness of bureaucratic is not yet reached. Keywords : Reform, Bureaucratic, Strategy